Saverio Muratori and the Italian school of planning typology - Cataldi, Giancarlo (2017)
This paper outlines the development of the Muratorian school of urban morphology and building typology. Starting from Muratori’s experience as a talented architect, deeply rooted in the Roman interpretation of Italian rationalism, the authors describe the growth of Muratori’ s interest in history as a means of recovering a sense of continuity in architectural practice. Adopting a theoretical approach grounded in architecture and urban design, he started working on a critical framework which could explain the creation and transformation of urban form over the centuries. He had many followers. The resurgence of interest in Muratori’s work in the 1990s is described.